Performance of Pregnant Mare Serum Gonadotropin and Vitamin Mix in Inducing Striped Catfish Pangasianodon hypophthalmus Rematuration - Syifania Hanifah Samara; Citra Fibriana; Uthami Nagin Lestari; Agus Oman Sudrajat (Jurusan Perikanan dan Kelautan, 2019)
The research aimed to assess the performance of Pregnant Mare Serum Gonadotropin (PMSG) and Human Chorionic Gonadotropin (HCG) hormone injection combined with vitamin mix to induce the rematuration of Striped catfish Pangasianodon hypophthalmus broodstock. Three PMSG and HCG treatments of 5 and 2,5 IU; 10 and 5 IU;also 20 and 10 IU/kg of broodstock body weight dosage combined with vitamin mix addition to fish feed and one control was used with four replications. The broodstock was reared for four weeks and weekly sampling for GR and SGR as well as hormone injection were performed. For the following two weeks, the broodstock was observed for maturation. Artificial spawning was conducted for broodstock reaching gonadal maturity. Statistic analysis of observed variables showed insignificant differences among the three treatments in rematuration parameters. The rematuration rate resulted in a 100% pregnancy. Broodstock treated with 10 IU PMSG and 5 IU HCG/kg of spawner body weight was able to reach maturity and spawned with the larval survival rate on the fourth day at 84,81%, thus it can be concluded that 10 IU PMSG and 5 IU HCG/kg of body weight as the best dosage.